China in Laos: Enclave spaces and the transformation of borders in the Mekong Region - Laungaramsri, Pinkaew (The Australian journal of anthropology, 2019)
Where China Meets Southeast Asia: Social and Cultural Change in the Border Regions edited by Grant Evans et al., is among the few works that take borderlands between China and mainland Southeast Asia seriously. A major contribution of this collection of border studies is its attempt to understand how border experiences and the process of bordering have changed since the early 1990s. Various Chinese–local interactions are explored in this book, with an emphasis on complex local responses to border transformations and diverse forms of mobility and network building. This article further examines the role of China and the Lao state, and the new wave of Chinese movement at the border. In establishing an economic integration that spills across the region, the penetration of Chinese power has been effective. The consequent retreat of the Lao state at the border has not only put an end to the old frontier but turned various borderlands into an estranged space of neoliberal enclave.